Vase life studies in Dracaena fragrans cv. ‘Massangeana’ as influenced by storage conditions and packaging materials - T.V., Anupama; Lakshmi, Amrutha (Journal of Tropical Agriculture, 2025)
Dracaena fragrans cv. ‘Massangeana’, belonging to the family Asparagaceae is one of the most exported foliage plants from India. The present study was undertaken with the objective to standardise appropriate storage condition and packaging materials to extend the vase life of Dracaena fragrans cv. ‘Massangeana’. After harvest, the leaves were subjected to various precooling treatments and the best treatment was subjected to packaging and storage studies viz., using polyethylene and polypropylene as packaging materials and storage in both cold storage and refrigerated conditions. Packaging in polypropylene sleeves with no perforations and storage for one week under cold storage conditions resulted in a better vase life (20.50 days). A minimum percentage loss in weight (18.64%) was observed in leaves stored under cold storage conditions after packing in perforated polyethylene sleeves. The chlorophyll content among the leaves was found to be maximum in leaves packed in polypropylene sleeves and stored under cold storage conditions (1.95 mg g-1). The highest rate of respiration after one week of storage was observed in leaf samples stored in refrigerated condition without any packaging material (1.25%). The study revealed that packaging Dracaena fragrans cv. ‘Massangeana’ leaves in polypropylene sleeves with no perforations and storage for one week under cold storage conditions resulted in better vase life and reduced metabolic activities, which can be utilised to enhance the export potential of the leaves.